2014
DOI: 10.1080/1059924x.2014.917350
|View full text |Cite
|
Sign up to set email alerts
|

Social Marketing Campaign Promoting the Use of Respiratory Protection Devices Among Farmers

Abstract: This article describes the formal use of marketing concepts in a systematic approach to influence farmers to voluntarily increase respiratory protective device (RPD) use. The planning process for the project incorporated six key decision or action points, each informed by formative research or health behavior theory. The planning process included developing behavior change strategies based on a 4P model (product, price, place, and promotion). The resulting campaign elements included print and e-mail messages t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 26 publications
0
20
0
Order By: Relevance
“…One study in the included studies assessed an intervention to improve the use of dust controls (Weidman et al 2016 ), and seven studies researched ways to improve the use of respirators (Adewoye et al 2014 ; Chen et al 2019 ; Donham et al 2011 ; Pounds et al 2014 ; Robertsen et al 2020 ; Shamsi et al 2016 ; Woith et al 2015 ). One hundred twenty-five studies evaluated dust control measures, as detailed in Supplementary Sheet 2 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One study in the included studies assessed an intervention to improve the use of dust controls (Weidman et al 2016 ), and seven studies researched ways to improve the use of respirators (Adewoye et al 2014 ; Chen et al 2019 ; Donham et al 2011 ; Pounds et al 2014 ; Robertsen et al 2020 ; Shamsi et al 2016 ; Woith et al 2015 ). One hundred twenty-five studies evaluated dust control measures, as detailed in Supplementary Sheet 2 .…”
Section: Resultsmentioning
confidence: 99%
“…Three studies (Adewoye et al 2014 ; Donham et al 2011 ; Pounds et al 2014 ) published before 2015 evaluated interventions to improve the use of PPE, whereas four similar studies were published from 2015 onwards (Chen et al 2019 ; Robertsen et al 2020 ; Shamsi et al 2016 ; Woith et al 2015 ).…”
Section: Resultsmentioning
confidence: 99%
“…Our results are consistent with current literature on the topic. Previous studies on apprentices and practicing farmers [32][33][34], hairdressers [35][36][37] and welders [38,39] have reported that knowledge about preventive measures varies from poor to average, the use of PPE is low, and several types of interventions tend to increase the level of knowledge and compliance with preventive measures. Kim et al [32] demonstrated in a pilot study among farmers that one educational workshop consisting of rotating stations with information on causes of work-related asthma, spirometry and use of PPE, aiming at increasing the knowledge about safety training and occupational health and safety (OHS) was feasible and effective, while Levesque et al [33] showed that farmers who received traditional pesticide safety training were more likely to use PPE; however, their confidence intervals were wide due to low number of participants.…”
Section: Discussionmentioning
confidence: 99%
“…Kim et al [32] demonstrated in a pilot study among farmers that one educational workshop consisting of rotating stations with information on causes of work-related asthma, spirometry and use of PPE, aiming at increasing the knowledge about safety training and occupational health and safety (OHS) was feasible and effective, while Levesque et al [33] showed that farmers who received traditional pesticide safety training were more likely to use PPE; however, their confidence intervals were wide due to low number of participants. Meanwhile, Pounds et al [34] implemented a different kind of intervention: a social media campaign promoting the use of respiratory protection devices (RPD) among farmers, and results showed that communication via e-mail increased knowledge about RPD, as well as intention to use these devices in dusty conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The programmes covered a variety of health and social issues. Twenty-five programmes focused on health-related issues, such as promoting testing for HIV and Chlamydia (Adam et al, 2016;Friedman et al, 2014); promoting health-related products such as condoms, sun protection, and respiratory protective devices (Liu et al, 2016;Purdy, 2011;Pounds et al, 2014;Potente et al, 2011); aiming to reduce alcohol consumption (Atkinson et al, 2011;Thompson et al, 2012); promoting organ donation (Brzeziński and Klikowicz, 2015); promoting health knowledge such as preconception, heart disease, and vaccination (Dixon-Gray et al, 2013;Taubenheim et al, 2008;La Torre et al, 2014); promoting a healthy lifestyle (increasing physical activity, or addressing obesity, eating habits, prevention of type 2 diabetes) (Woolley and Peterson, 2012;Frerichs et al, 2015;Gase et al, 2015;George et al, 2016;James et al, 2013;Khurshid et al, 2015;Picazo-Vela et al, 2016;Rogers et al, 2017, Tobey andManore, 2014); promoting health resources (tobacco quit-line, mental health resources, and cancer survivors health resources) (Kennedy et al, 2013;Nicholas, 2010;Justice-Gardiner et al, 2012); and preventing drug abuse (Macario et al, 2013). Only four programmes covered social issues, such as reducing stigma and discrimination against individuals with mental health issues (Evans-Lacko et al, 2013;Sampogna et al, 2017), reducing stigma against LGBT individuals (Adam et al, 2011;Hull et al, 2017), and reducing adolescent dating abuse (Lambert et al, 2014).…”
Section: Programme Overviewmentioning
confidence: 99%